Biochemical comparison of commonly cultivated mushroom types of Kerala - Zacharia, R M; Rakhie, N; Deepa, K; Leenakumary, S (Mushroom Research, 2017)
The present study was conducted with a view to assess the commonly cultivated mushroom types of Kerala based on nutrient composition. Results of studies using five types grown on chemically sterilized paddy straw revealed that pink mushroom (Pleurotuseous) was nutritionally superior as it contained lowest carbohydrate (2.59g %), higher protein (2.72g %) and dietary fiber (2.9g %) compared to all other varieties. It also contained the higher quantity of all the essential amino acids except valine than P. florida. But for minerals, P.sajor-cajuwas superior as it contained the highest quantity of sodium (100 ppm), potassium (3300 ppm), calcium (11.8ppm), magnesium (191 ppm), iron (75.26 ppm) and zinc (29.27 ppm). The antioxidant selenium (0.87 ppm) was present only in this type. An experiment was conducted using three varieties in order to determine whether the nutrients varied with substrates. Mushrooms from rubber wood sawdust beds showed an increased value with respect to carbohydrates, protein, and fat. Fiber content was less for mushrooms from sawdust for P.eous and Hypsyzygussp. In the studies using different modes of sterilization for substrates, mushrooms from steam sterilized paddy straw beds recorded higher quantity of carbohydrates, fiber, and pH. Increased content of calcium, magnesium, and zinc was noted in P.florida and P.eous.In another study at different stages of maturity, P.eous harvested on the first day after pinhead formation showed increased quantity of carbohydrates (6.39g%), fat (0.4g%) and minerals like sodium (82 ppm), potassium (3320 ppm), calcium (84 ppm) and iron (30 ppm). Calcium showed a drastic reduction on the third day after pinhead formation. Results showed that proximates, minerals, and amino acids varied with mushroom varieties, substrates, type of sterilization and days for maturity.